IMPLEMENTASI STRATEGI MITIGASI DAMPAK EL NIÑO PADA PERTANIAN PADI - Marina, Ida; Sumantri, Kosasih; Mushtaq, Zain; Umyati, Sri (AGROSCIENCE (AGSCI), 2024)
This study aims to assess the impact of El Niño's extreme climate on rice farming in Jatitengah Village, Majalengka Regency, as well as mitigation efforts undertaken by farmers in the face of its negative impacts. Primary data were collected through interviews, questionnaires, and personal notes with farmers, while secondary data came from literature studies. Respondents consisted of 88 rice farmers selected using a simple random sample method.The results showed that farmers in Jatitengah Village have a high level of awareness towards mitigating the negative impacts of El Niño on rice farming. Most farmers have adopted various mitigation components, such as adjustments to cropping patterns, the use of superior varieties, no-burn management, and irrigation techniques. However, there are still some mitigation components that have not been fully adopted by farmers, such as organic fertilizer, land rehabilitation, and access to funding for afforestation and land rehabilitation. The results show that efforts to mitigate the negative impacts of El Niño on rice farming in Jatitengah Village have progressed, but further efforts are still needed to increase farmers' awareness and participation in implementing broader and more effective mitigation strategies.